Combination of paclobutrazol, potassium sulfate and Ethephon on floral induction of mango cv. Tommy Atkins - Silva, José Algaci Lopes da; Neves, Josynaria Araújo (Comunicata Scientiae, 2011)
Amongst the techniques used for the regulation of the vegetative growth of mango trees with the purpose in floral induction, is common the arranged use of the substances Paclobutrazol, Potassium Sulfate and Ethephon. Under conditions of semi-arid tropic the precipitated technique has persuaded an abundant flower induction, however has produced inconsistent effects in the conditions of warm and rainy climate. With the purpose to study that combination in the growth e flowering of mango trees, variety Tommy Atkins, it was experimented in the mesorgion of Teresina City, State of Piauí, under conditions of humid tropic, using an experimental design of randomized complete blocks, with an factorial arrangement 4 x 3: four Paclobutrazol doses (zero; 0.7; 1.0 and 1.3 g of a.i. m-1 of diameter tree canopy) and three practices that combined applications of Potassium Sulfate (2%), Ethephon (240 ppm) on three periods of floral induction, 90, 105 and 120 days, to the start of application of dormancy-breaking, which was counted from the Paclobutrazol application. Plants untreated produced only vegetative branches and the various products and periods of applications combinations tested showed low rates flowering and high rates of dormant buds.